2020
DOI: 10.3390/nu12092760
|View full text |Cite
|
Sign up to set email alerts
|

Cooking for Vitality: Pilot Study of an Innovative Culinary Nutrition Intervention for Cancer-Related Fatigue in Cancer Survivors

Abstract: (1) Background: Cancer-related fatigue (CRF) is one of the most prevalent and distressing side effects experienced by patients with cancer during and after treatment, and this negatively impacts all aspects of quality of life. An increasing body of evidence supports the role of poor nutritional status in the etiology of CRF and of specific diets in mitigating CRF. We designed a group-based two session culinary nutrition intervention for CRF, Cooking for Vitality (C4V), aimed at increasing understanding of how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 82 publications
1
15
0
Order By: Relevance
“…75 In patients with cancer, group Culinary Medicine interventions improved not only healthy eating choices but also the quality of life and well-being, 76 highlighting the potential for a layered physical and emotional impact of hands-on Culinary Medicine in various disease states. Pritlove et al 77 similarly found that a cooking intervention improved cancer-related fatigue and significantly reduced disability scores.…”
Section: Culinary Medicine and Kidney Diseasementioning
confidence: 96%
“…75 In patients with cancer, group Culinary Medicine interventions improved not only healthy eating choices but also the quality of life and well-being, 76 highlighting the potential for a layered physical and emotional impact of hands-on Culinary Medicine in various disease states. Pritlove et al 77 similarly found that a cooking intervention improved cancer-related fatigue and significantly reduced disability scores.…”
Section: Culinary Medicine and Kidney Diseasementioning
confidence: 96%
“…CRF is prevalent and debilitating for cancer survivors. In the last decade, there has been a surge in research focused on identifying CRF risk factors and potential interventions to target these etiological factors [ 143 ]. Studies examining links between CRF and dietary inflammation largely support the hypothesis that inflammatory processes contribute to fatigue during and after cancer treatment [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, some patients expressed frustration in being provided with information when it did not translate to them having the con dence and skills to act on recommendations provided. A culinary intervention program developed for patients with cancer related fatigue found that access to experiential learning in the form of face to face and online cooking classes improved participants cooking skills, providing them with greater con dence to achieve their nutritional intake [36]. Furthermore, the use of visual aids including illustrations and videos can help patients have a greater understanding of information provided [37].…”
Section: Discussionmentioning
confidence: 99%